2007
DOI: 10.1016/j.brainres.2007.07.004
|View full text |Cite
|
Sign up to set email alerts
|

Effects of season, testosterone and female exposure on c-fos expression in the preoptic area and amygdala of male green anoles

Abstract: Expression of the immediate early gene, c-fos, was used to investigate changes in neuronal activity in forebrain regions involved in male sexual behavior following social, hormonal and/or seasonal manipulations in the male green anole. These factors all influence behavior, yet it is unclear how they interact to modify neuronal activity in forebrain regions, including the preoptic area (POA) and ventromedial nucleus of the amygdala (AMY). These regions are involved in the display of sexual behaviors in male gre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
9
0

Year Published

2009
2009
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 70 publications
1
9
0
Order By: Relevance
“…Evidence from neuroendocrine studies in lizards suggest that T alters the activity of neurotransmitter systems that may modulate motivation for social interaction and sexual behavior (Neal and Wade, 2007;Wade, 2011;O'Connell et al, 2012). Our results in G. lichtenfelderi support this idea because castrated males were active in the neutral arena but not as motivated to interact with the female compared to males with elevated T levels.…”
Section: Effect Of Test Venue On Likelihood Of Male Sexual Behavior Esupporting
confidence: 86%
“…Evidence from neuroendocrine studies in lizards suggest that T alters the activity of neurotransmitter systems that may modulate motivation for social interaction and sexual behavior (Neal and Wade, 2007;Wade, 2011;O'Connell et al, 2012). Our results in G. lichtenfelderi support this idea because castrated males were active in the neutral arena but not as motivated to interact with the female compared to males with elevated T levels.…”
Section: Effect Of Test Venue On Likelihood Of Male Sexual Behavior Esupporting
confidence: 86%
“…For example, Tetel et al [89] and Pfaus et al [70] observed decreases in the induction of FOS-IR following small amounts of vaginocervical stimulation in the VMH when female rats were treated with estradiol. In addition, a decrease in immediate early gene expression in the preoptic area and amygdala occurs following testosterone administration in male anole lizards [59]. …”
Section: Discussionmentioning
confidence: 99%
“…Bailey et al, 2002;Neal and Wade, 2007;Huang et al, 2013], as well as other amphibians (i.e. the salamander Plethodon shermani [Laberge et al, 2008] and Xenopus laevis [Calle et al, 2006]).…”
Section: Analysis Of the Ieg Neural Activity Associated With Geometrymentioning
confidence: 99%
“…We also examined the amygdala and the bed nucleus of the stria terminalis, both of which were characterized by low numbers of labeled cells (not reported) that visually did not vary across the three treatment groups. Only complete diameter and clearly stained nuclei were counted, following closely the procedures of Neal and Wade [2007].…”
Section: Analysis Of the Ieg Neural Activity Associated With Geometrymentioning
confidence: 99%